Rapunzel syndrome in a boy: A case report with review of literature of boys with Rapunzel syndrome - Kuldeep Singh; Pawan Kapoor; Nishu Grover; Surendra Godara (Wolters Kluwer Medknow Publications, 2023)
Background: Trichobezoar is a rare phenomenon where a ball of swallowed hair collects in the stomach. When its tail extends beyond the pylorus in to the small intestine, it is termed Rapunzel syndrome. The condition is most commonly seen in females with psychological disturbances, many of whom have trichotillomania and or trichophagia. We report Rapunzel syndrome condition in a young boy having no overt mental disturbances. Clinical Description: A 5½-year-old male child presented with complaints of vomiting for 20 days, associated with dull aching epigastric pain over 1 year. A lump had been noticed in the abdomen which was increasing in size for the past 5 months and decreased appetite for past 1 month. Besides pica, the child had no other significant medical or surgical illness. On examination, the child was underweight with pallor, with dry, lusterless, easily pluckable hair. His abdomen revealed a palpable lump in epigastrium, with ultrasonography showing a large gastric mass with air foci. Contrast-enhanced computed tomography abdomen revealed a large, well-circumscribed, nonhomogeneous lesion in the lumen of the stomach suggestive of bezoar. The patient underwent exploratory laparotomy, which confirmed trichobezoar with a long tail of hair extending through the pylorus into the small bowel. After successful removal of the trichobezoar, the patient was discharged with no postoperative complication and advised follow up in surgery, pediatrics, and psychiatry department. Conclusion: This case creates awareness of the possibility of the rare, bizarre entity of trichobezoar in a toddler presenting with nothing more than the usual common symptoms as seen in this age group. After ruling out common causes, when there is persistence of symptoms, with some clinical clues like pica, anemia, and behavior abnormalities, pediatricians may suspect an underlying atypical diagnosis like trichobezoar, even in a male child.